THE RELATION OF THE MOTHER'S KNOWLEDGE AND ATTITUDE OF DIARRHEA TREATMENT AT INTEGRATED HEALTH POST KALIBATUR KALIDAWIR TULUNGAGUNG - Farida (NurseLine Journal, 2016)
Diarrhoea diseases is still a health problem in Indonesia, it can be seen from the high morbidity and mortality as well as the extraordinary events that are often encountered in the community. Diarrheal disease more dominant in children under five than in adults because her immune system is still weak. But there are a lot of mothers who have not been sufficiently able to provide good handling, this is because knowledge about the treatment of diarrhea in infants is low so it will affect the attitude in the treatment of diarrhea in children. This study aims to determine the relationship of knowledge about diarrhea with mothers attitude in diarrhea treatment. This type of research is an analytic correlation with cross sectional study. The study population is mothers in Integrated. Health Post Kalibatur with total sampling technique with a number of 30 respondents. The result showed that 30 respondents were 21 (70%) of mothers who have a good